Explaining entrepreneurial intentions by means of the theory of planned behavior - Van Gelderen, Marco; Brand, Maryse; van Praag, Mirjam; Bodewes, Wynand; Poutsma, Eric; van Gils, Anita (Emerald Group Publishing Limited, 2006)
This paper provides a detailed explanation of entrepreneurial intentions among business students. The Theory of Planned Behavior (TPB) is employed, which regards intentions as resulting from attitudes, perceived behavioral control, and subjective norms. Our main study is replicated among samples of undergraduate students of business administration at four different universities (total N=1225). We use five operationalizations of intentions, as well as a composite measure. Prior to our main study the components of the TPB were operationalized based on qualitative work at yet two other universities (total N=373). The results show that the two variables that most consistently explain entrepreneurial intentions are entrepreneurial alertness, and the importance attached to financial security.
Keywords: Entrepreneurial Intentions; Business start-up; Entrepreneurial career choice; Theory of planned behavior; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management